Are You Sure this is a Fair Spinner?

Three players play a game in which they take turns spinning a spinner with three different colors. Each player is assigned a color and takes a turn spinning the spinner until he or she spins his or her color and wins the game.

The spinner is designed so that the player who goes first, the player who goes second, and the player who goes third all have an equal probability of winning the game. If x x is the percentage of the largest color on the spinner, then x x is a solution to the cubic equation A x 3 + B x 2 + C x = 1 Ax^3 + Bx^2 + Cx = 1 . Find A + B + C A + B + C .

Inspiration


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chris Lewis
May 14, 2019

Let p i p_i be the probability player i i wins on a single spin (ie, the proportion of the spinner assigned to them) and let P i P_i be their probability of winning overall.

Let L = ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) L=(1-p_1)(1-p_2)(1-p_3) be the probability that in any given round, no-one wins.

We have P 1 = p 1 + L p 1 + L 2 p 1 = p 1 1 L P_1=p_1+Lp_1+L^2 p_1 \ldots=\frac{p_1}{1-L}

P 2 = ( 1 p 1 ) p 2 + L ( 1 p 1 ) p 2 + L 2 ( 1 p 1 ) p 2 = ( 1 p 1 ) p 2 1 L P_2=(1-p_1)p_2+L(1-p_1)p_2+L^2 (1-p_1)p_2 \ldots=\frac{(1-p_1)p_2}{1-L}

P 3 = ( 1 p 1 ) ( 1 p 2 ) p 3 + L ( 1 p 1 ) ( 1 p 2 ) p 3 + L 2 ( 1 p 1 ) ( 1 p 2 ) p 3 = ( 1 p 1 ) ( 1 p 2 ) p 3 1 L P_3=(1-p_1)(1-p_2)p_3+L(1-p_1)(1-p_2)p_3+L^2 (1-p_1)(1-p_2)p_3 \ldots=\frac{(1-p_1)(1-p_2)p_3}{1-L}

Since we want the P i P_i to be equal, this just becomes

p 1 = ( 1 p 1 ) p 2 = ( 1 p 1 ) ( 1 p 2 ) p 3 p_1=(1-p_1)p_2=(1-p_1)(1-p_2)p_3

The largest portion of the spinner will be assigned to Player 3 3 ; so x = p 3 x=p_3 .

Cancelling and rearranging the above, we find

p 1 = x 1 + 2 x p_1 = \frac{x}{1+2x} and p 2 = x 1 + x p_2 = \frac{x}{1+x}

Since p 1 + p 2 + p 3 = 1 p_1+p_2+p_3=1 , we have

x 1 + 2 x + x 1 + x + x = 1 \frac{x}{1+2x}+\frac{x}{1+x}+x=1

Clearing denominators, this is 2 x 3 + 4 x 2 = 1 2x^3+4x^2=1 , so ( A , B , C ) = ( 2 , 4 , 0 ) (A,B,C)=(2,4,0) and the answer is 6 \boxed6 .

David Vreken
Apr 6, 2019

Let p 1 p_1 be the percentage of Player 1's spinner, p 2 p_2 be the percentage of Player 2's spinner, and p 3 p_3 be the percentage of Player 3's spinner. Player 3 has the disadvantage of going last, so to have an equal probability of winning the game, his percentage of the spinner will be the biggest, therefore we are trying to find x = p 3 x = p_3 .

All three percentages must add up to the whole spinner, so

p 1 + p 2 + p 3 = 1 p_1 + p_2 + p_3 = 1

Let q 1 q_1 be the overall probability of Player 1 winning. Player 1 has a p 1 p_1 chance of winning on the first spin and has a ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) (1 - p_1)(1 - p_2)(1 - p_3) chance of everyone else not spinning their correct color so that the game can start over again. Therefore, q 1 = p 1 + ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) q 1 q_1 = p_1 + (1 - p_1)(1 - p_2)(1 - p_3)q_1 . Since there are 3 3 people playing, each player must have a 1 3 \frac{1}{3} probability of winning, so q 1 = 1 3 q_1 = \frac{1}{3} . Therefore, 1 3 = p 1 + ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) 1 3 \frac{1}{3} = p_1 + (1 - p_1)(1 - p_2)(1 - p_3)\frac{1}{3} or

1 3 ( 1 ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) ) = p 1 \frac{1}{3}(1 - (1 - p_1)(1 - p_2)(1 - p_3)) = p_1

By a similar argument, let q 2 q_2 be the overall probability of Player 2 winning. Player 2 has a 1 p 1 1 - p_1 chance of Player 1 not spinning his correct color and a p 2 p_2 chance of winning on his first spin, and then a ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) (1 - p_1)(1 - p_2)(1 - p_3) chance of everyone else not spinning their correct color so that the game can start over again. Therefore, q 2 = ( 1 p 1 ) p 2 + ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) q 2 q_2 = (1 - p_1)p_2 + (1 - p_1)(1 - p_2)(1 - p_3)q_2 . Since there are 3 3 people playing, each player must have a 1 3 \frac{1}{3} probability of winning, so q 2 = 1 3 q_2 = \frac{1}{3} . Therefore, 1 3 = ( 1 p 1 ) p 2 + ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) 1 3 \frac{1}{3} = (1 - p_1)p_2 + (1 - p_1)(1 - p_2)(1 - p_3)\frac{1}{3} or

1 3 ( 1 ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) ) = ( 1 p 1 ) p 2 \frac{1}{3}(1 - (1 - p_1)(1 - p_2)(1 - p_3)) = (1 - p_1)p_2

From the last two equations, 1 3 ( 1 ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) ) = p 1 = ( 1 p 1 ) p 2 \frac{1}{3}(1 - (1 - p_1)(1 - p_2)(1 - p_3)) = p_1 = (1 - p_1)p_2 , so p 2 = p 1 1 p 1 p_2 = \frac{p_1}{1 - p_1} . Substituting this into the first equation we have p 1 + p 1 1 p 1 + p 3 = 1 p_1 + \frac{p_1}{1 - p_1} + p_3 = 1 which solves to p 1 = 1 2 ( 3 p 3 p 3 2 2 p 3 + 5 ) p_1 = \frac{1}{2}(3 - p_3 - \sqrt{p_3^2 - 2p_3 + 5}) .

Then after substituting p 2 = p 1 1 p 1 p_2 = \frac{p_1}{1 - p_1} and then p 1 = 1 2 ( 3 p 3 p 3 2 2 p 3 + 5 ) p_1 = \frac{1}{2}(3 - p_3 - \sqrt{p_3^2 - 2p_3 + 5}) into 1 3 ( 1 ( 1 p 1 ) ( 1 p 2 ) ( 1 p 3 ) ) = p 1 \frac{1}{3}(1 - (1 - p_1)(1 - p_2)(1 - p_3)) = p_1 , this solves to the cubic equation 2 p 3 3 + 4 p 3 2 = 1 2p_3^3 + 4p_3^2 = 1 , so A = 2 A = 2 , B = 4 B = 4 , C = 0 C = 0 , and A + B + C = 6 A + B + C = \boxed{6} .


Note : the numerical approximations for p 1 p_1 , p 2 p_2 , and p 3 p_3 are p 1 0.237286 p_1 \approx 0.237286 , p 2 0.311108 p_2 \approx 0.311108 , and p 3 0.451606 p_3 \approx 0.451606 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...